Magnetohydrodynamics CU˗TiO2 hybrid nanofluid with viscous dissipation - Rahimah, Jusoh; Zulkhibri, Ismail; Muhammad Khairul Anuar, Mohamed; Nooraini, Zainuddin (Penerbit UTM Press, 2024)
Boundary layer flow is often described as a thin layer filled with fluid that is next to a solid object’s surface. Within this layer, fluid properties undergo rapid changes because of how the fluid and solid surface interact. Recently, there had many studies on the boundary layer flow across a stretching/shrinking plate due to numerous applications in various industrial and technical sectors. The manufacturing of glass fibre, aerodynamic plastic sheet extrusion, metal spinning, condensation of metallic plates, wire drawing, and hot rolling are a few examples of these uses. Prandtl number (Pr), was a pioneer in presenting the concept of the boundary layer, where he suggested that friction causes the fluid directly in contact with a surface to adhere to it, which is called the no-slip condition. He proposed that the influence of friction was primarily confined to the boundary layer, which is a thin layer near the surface, while the flow beyond this layer was nearly inviscid, akin to the flow discussed for centuries prior (Anderson, 2005). Crane (1970), started the examination of the flow past an elongated plate and offered an analytical answer. Afterwards, abundant academics expanded on the model by considering a variety of conditions.